Playing on Two Chessboards: Reputation Effects between Corporate Social Responsibility (CSR) and Corporate Political Activity (CPA) - den Hond, Frank; Rehbein, Kathleen A.; de Bakker, Frank G. A.; Lankveld, Hilde Kooijmans-van (Journal of management studies, 2014)
It has recently been argued that corporate social responsibility (CSR) is ‘political’. It has been neglected however, that firms also operate politically in a traditional sense, in seeking to secure favourable political conditions for their businesses. We argue that there are potential synergies between CSR and corporate political activity (CPA) that are often overlooked by firms and that recognition of these synergies will stimulate firms to align their CSR and CPA. We develop a conceptual model that specifies how various configurations of a firm's CSR and CPA – alignment, misalignment, and non‐alignment – affect the firm's reputation beyond the separate reputation effects of CSR and CPA. This model has important implications for understanding how and why firms should pay attention to their CPA and CSR configurations, and thereby contributes to the broader issue of why firms should make sure that they are consistent in terms of responding to stakeholder concerns.